Faktor - Faktor Yang Mempengaruhi Mahasiswa Akuntansi Dalam Pemilihan Karier Profesi Akuntan - Sungkono Sungkono (EBBANK, 2012)
Many kinds of work which need the workers, will indirect to adapt with qualification of characteristic the occupation, one of them is qualification at accounting sector. The companies who need people have graduated from accounting majority, must be known all of the factors that is considered by the workers, when they accept some occupation. The number of accountant still rarely than Indonesian people now, and very possible, if the accountants profession will booming at the future, both of quality and quantity. This condition will bring to some consequence, that everyone can choose accountant to be the agreement profession. The profession of accountants are public accountant, management accountant, government accountant, education accountant, and consultant.            Researcher was use likert-scale questionnair for this research. Five factors comprising 20 questions concerning career choice factors were addressed. The five factors are job criteria, idealism, earnings, social responsibility, and job market. Employing a survey of 60 accounting students from state and private university. Multiple regression analysis was used to assess the ability of five factors to distinguish choose a career as accountant. T-test were used to compare responses of accounting students from state and private university, and also to compare responses of man and woman accounting students. The research result indicate that based on the absolute score, those opting are more concerned with all (five) factors that influence accounting students to choose kind of accountants profession as a career. However, based on the independent sample test, there is  differentiation between accounting students from state and private university to choose kind of accountants profession as a career, the resulted score that was statistically significant is from social responsibility factor. There isn’t differentiation between man and woman accounting students to choose kind of the accountants profession as a career. Accounting students in this research, mostly choose a management accountant as  their  career.